Igniting Motivation: Enhancing Writing through Strategy Training among Grade 11 Students - Tufa, Lalisa Leta; Metaferia, Tekle Ferede; Gizachew, Teshale Tefera (International journal of multicultural and multireligious understanding, 2025)
This quasi-experimental study investigated the effect of writing strategy training on enhancing motivation among Grade 11 students with 52 students in the experimental group receiving training in cognitive, metacognitive, memory, compensation, and social strategies, while 47 students in the control group followed conventional teaching. Data were collected through pre- and post-test questionnaires that supported by semi-structured interviews. The data were analyzed using independent and paired sample t-tests. The results revealed significant improvements in the experimental group’s writing self-efficacy, achievement goal orientation, writing beliefs, affective and overall motivation with all changes demonstrating large effect sizes. These findings indicate that strategy training is an effective approach for strengthening learners’ motivation and engagement in academic writing. Based on these results, the study recommends that teachers systematically integrate writing strategy training into classroom practice, curriculum developers embed motivational elements such as autonomy support and mastery-oriented goals into writing pedagogy and future researchers examine the long-term sustainability and applicability of such interventions across diverse educational contexts.